Brain endothelial cell‐targeted gene therapy of neurovascular disorders - Serena Marchiò; Richard L Sidman; Wadih Arap; Renata Pasqualini (EMBO Molecular Medicine)
Abstract Neurovascular disorders are difficult to treat due to the blood–brain barrier (BBB), which prevents delivery of most drugs from the blood into the brain. Gene therapy can potentially overcome this barrier, but classical vectors are neither efficient nor specific enough to provide long‐lasting treatment or avoid off‐target effects. In this issue of EMBO Molecular Medicine, Körbelin et al (2016) describe an engineered adeno‐associated virus (AAV) with exceptional tropism for the brain that restores a normal phenotype in a mouse model of incontinentia pigmenti (IP), a severe human genetic disorder of brain vasculature.